2013
DOI: 10.1063/1.4813481
|View full text |Cite
|
Sign up to set email alerts
|

Communication: The distinguishable cluster approximation

Abstract: The equation of motion coupled-cluster method. A systematic biorthogonal approach to molecular excitation energies, transition probabilities, and excited state properties The Journal of Chemical Physics 98, 7029 (1993) We present a method that accurately describes strongly correlated states and captures dynamical correlation. It is derived as a modification of coupled-cluster theory with single and double excitations (CCSD) through consideration of particle distinguishability between dissociated fragments, whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
129
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(132 citation statements)
references
References 32 publications
3
129
0
Order By: Relevance
“…Numerous authors have proposed methods that yield reasonable predictions in the presence of near degeneracies by modifying coupled cluster theory or variants thereof. [8][9][10][11][12][13][14][15][16][17][18][19][20] We would like a simple conceptual framework which allows us to identify the offending terms in traditional coupled cluster theory so that by excluding them we can avoid the downfall of the method. Of course, this is easier said than done, but we here show one particular case which substantially removes the typical failures in repulsive Hamiltonians.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous authors have proposed methods that yield reasonable predictions in the presence of near degeneracies by modifying coupled cluster theory or variants thereof. [8][9][10][11][12][13][14][15][16][17][18][19][20] We would like a simple conceptual framework which allows us to identify the offending terms in traditional coupled cluster theory so that by excluding them we can avoid the downfall of the method. Of course, this is easier said than done, but we here show one particular case which substantially removes the typical failures in repulsive Hamiltonians.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] In previous work along these lines, we found that separating the singlet-and triplet pairing channels of T 2 and isolating them from one another, giving singlet-paired (CC0) and triplet-paired coupled cluster (CC1), protected CC from blowup. [27,29] There, we decomposed T 2 along particle-particle/holehole (pp-hh), or ladder, channels, [30] eliminating the interaction of the channels completely.…”
Section: Introductionmentioning
confidence: 99%
“…Relaxing orbitals for DCD using Brueckner condition [10][11][12] was considered in Paper I. 8 Although a DCD wavefunction cannot be properly specified, one can formally assume that there is a DCD wavefunction containing only doubles, and then the orbitals are rotated such that the condition…”
Section: Theorymentioning
confidence: 99%
“…There are many attempts to develop methods capable to treat strong correlation in the single-reference framework. [2][3][4][5][6][7] Very recently we have proposed a method named the distinguishable cluster doubles (DCD) approximation, 8 which retains the simplicity and efficiency of the single-reference treatment, but is accurate and robust in the strongly correlated cases, e.g., in bond-breaking processes. Furthermore, even in single-reference cases the accuracy of DCD turned out to be superior to the conventional CCD counterpart.…”
Section: Introductionmentioning
confidence: 99%